Website-Based Learning Media in High School Biology Learning on Genetic Substance Material - Ega Safitri; Anna Rakhmawati (LPPM Undiksha, 2024)
Genetic substance material requires learning media in its delivery because it cannot be seen directly, making it difficult for students to understand. This study aims to create a website-based learning media suitable for high school biology learning on genetic substance material. The research method used is research and development (R&D) with the ADDIE model. The study subjects included material and media experts, teachers, and 13 grade XII high school students. Data collection was carried out using interview, observation, and questionnaire methods. Data analysis techniques used qualitative and quantitative analysis. The results of the study showed that the validation of material experts obtained a score of 100% (very feasible), media experts obtained a score of 87.50% (very possible), individual trials obtained a score of 100% (very possible), and limited trials obtained a score of 85.79% (very feasible). It was concluded that website-based learning media is suitable for application in biology learning on genetic substance material. The implications of this study are to motivate teachers to use media in the learning process at school.